Structural behavior of axially loaded high strength concrete columns reinforced longitudinally with glass fiber reinforced polymer bars - P, Sasikumar; R, Manju (Revista de la Construcción. Journal of Construction, 2023)
This study investigated the behaviour of axially loaded high strength concrete columns reinforced longitudinally with glass fibre reinforced polymer bars. Total six Reinforced Concrete (RC) columns and six Glass Fibre Reinforced Polymer (GFRP) reinforced concrete columns made with High Strength Concrete (HSC) with the addition of 1.20% of Alkali Resistant Glass Fibre (ARGF). The columns were cast with 1000 mm height and cross-sectional area is 150 mm x 150 mm and were tested under axial loading. The main objective of this study including to increase axial load carrying capacity and stiffness and reduce the ductility, mode of failure, and axial load-displacement response of columns. The RC columns are compared to the GFRP RC columns, and the GFRP RC columns are only carried 90% of the axial load compared to the RC columns. The Finite Element Model (FEM) was used to analyses all columns, and FEM helps predict the axial load.